ANALISIS USABILITY MODEL ISO 9241-11 DENGAN PENDEKATAN PERFORMANCE MEASUREMENT, RETROSPECTIVE THINK ALOUD, DAN SYSTEM USABILITY SCALE PADA SISTEM INFORMASI - Deluma, Abdul Rahman; Syahrial, Syahrial; Maku, Rubiyanto (Jurnal Ilmu Komputer (JUIK), 2023)
This research was conducted to evaluate the SIKKD UMGO website by highlighting the three usability concepts of the ISO 9241-11 model, namely effectiveness, efficiency, and user satisfaction in using the SIKKD website, measured using the Usability Testing methods: Performance Measurement, Retrospective Think Aloud (RTA), and System Usability Scale techniques. The aim is to find out the results of usability testing and recommendations for improvements to the SIKKD website based on the results of usability testing. The results of this study are based on an analysis of the calculation of usability metrics, and the SUS formula shows that the effectiveness and efficiency aspects have been stated to be good, namely the percentages of 98% and 95%. In addition, the satisfaction aspect based on the SUS questionnaire is still below standard with a percentage value of 59%. The SUS results are supported by the results of the RTA questionnaire, where there are still several complaints and suggestions from respondents on the SIKKD website. Based on the results of the SUS and RTA questionnaires, recommendations for improvements were made in the form of prototypes on login pages, resumes, forms, file uploads, and account settings by following the 4 golden rules of user interface design.